2004
DOI: 10.4049/jimmunol.172.8.4804
|View full text |Cite
|
Sign up to set email alerts
|

CD40 Ligation In Vivo Induces Bystander Proliferation of Memory Phenotype CD8 T Cells

Abstract: Injection of agonistic anti-CD40 Abs into mice has been shown to amplify weak CD8 T cell responses to poorly immunogenic compounds and to convert T cell tolerance to T cell priming. In this study we demonstrate that anti-CD40 treatment of C57BL/6 mice, without Ag delivery, led to a marked increase in the number of memory phenotype CD4 and CD8 T cells. Adoptive transfer experiments using CD40-deficient hosts further revealed that the proliferative response of memory T cells, induced by systemic CD40 signaling, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 52 publications
0
21
0
2
Order By: Relevance
“…Many researchers have reported that administration of TLR ligands such as LPS, polyinosinic:polycytidylic acid, and CpG DNA induces proliferation of memory CD8 ϩ T cells through production of cytokines involving type I IFNs, IL-12, IL-15, and IL-18 [5,35]. It was demonstrated that the cytokine-dependent bystander activation was sufficient to induce IFN-␥ production from memory T cells in vivo [6 -8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many researchers have reported that administration of TLR ligands such as LPS, polyinosinic:polycytidylic acid, and CpG DNA induces proliferation of memory CD8 ϩ T cells through production of cytokines involving type I IFNs, IL-12, IL-15, and IL-18 [5,35]. It was demonstrated that the cytokine-dependent bystander activation was sufficient to induce IFN-␥ production from memory T cells in vivo [6 -8].…”
Section: Discussionmentioning
confidence: 99%
“…sLe x antigen-expressing and sLe x antigen-negative CD4 ϩ T (A) or CD8 ϩ T (B) cells were isolated by the FACSVantage cell sorting system. The isolated cells (1ϫ10 5 ) were cultured in the presence of IL-2 (20 U/mL) plus IL-15 (20 ng/mL) or IL-12 (50 U/mL) for 3 days. IFN-␥ levels in culture supernatants were determined by ELISA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with IL-12, CD40 and NKG2D ligation could be involved in the stimulation of memory CD8 + T cells (40)(41)(42). In the present model, we ruled out the involvement of MHC class I recognition (classical or nonclassical MHC class I molecules, such as Qa-1, a MHC-Ib product) in the activity of regulatory CD8 + T cells, because semiallogeneic DC-stimulated CD8 + T cells were able to inhibit Th2 cytokine production and OVA-specific IgE production when transferred to OVA-sensitized b2m-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo regulation of bystander expansion is likely to be both complex and highly dynamic and controlled by cytokines and costimulatory receptor-ligand interactions (4,5,11,13,26), and many of these parameters remain to be fully evaluated in our model. However, it is known that there is increased accumulation of IL-2 mRNA in mice with chronic L. donovani infections (6), and more recent preliminary studies indicate that IL-7 mRNA accumulation was not altered, while IL-15 mRNA accumulation was reduced in the spleens of infected mice compared to the spleens of naïve mice (Polley, unpublished data).…”
Section: To Determine How L Donovani Infection Affected Established Cd8mentioning
confidence: 99%